OPTIMIZATION OF HUMAN RESOURCE MANAGEMENT STRATEGIES TO ENHANCE JOB SATISFACTION IN STARTUP COMPANIES - Nurhab, Badaruddin; Nurhab, Muhamad Irpan; Aziz, Syaefudin; Huda, Nurul (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2025)
In the digital era marked by rapid dynamics and uncertainty, startup companies face unique challenges in managing human resources (HR). This study aims to analyze effective HR management strategies to enhance employee job satisfaction within startup environments. Using a qualitative approach through case studies and in-depth interviews across various sectors, the research identifies five key factors that significantly contribute to job satisfaction: work flexibility, a positive organizational culture, career development opportunities, fair reward and incentive systems, and open communication between management and employees. These strategies have been shown to foster employee loyalty, enhance motivation, and strengthen productivity amid limited resources and the fast-paced changes characteristic of startups. The findings offer practical insights for startup leaders in designing adaptive HR policies and contribute to the academic literature on contemporary HR management.